From molecules in solution to molecules on surfaces – using supramolecular dyads to form functional self-assembled networks on graphene. Issue 37 (19th August 2022) - Fernez, Quentin; Moradmand, Shiva; Mattera, Michele; Djampa-Tapi, William; Fiorini-Debuisschert, Céline; Charra, Fabrice; Kreher, David; Mathevet, Fabrice; Arfaoui, Imad; Vargas, Lydia Sosa
Abstract : The formation of supramolecular dyads that can form ordered, 2D-assemblies on graphene is an intricate process. Using different molecular components allows us to control the positioning of the emissive unit in relation to the graphene substrate. Abstract : Using supramolecular chemistry to functionalise graphene for photonic applications is a challenging issue due to graphene's capacity to quench any emission from molecules adsorbed on its surface. To overcome this problem, we propose the use of molecular dyads to form ordered self-assemblies on graphene-like substrates. These dyads are designed to reduce surface quenching by positioning the emissive component out-of-the plane of the substrate. We use a zinc porphyrin and a phthalocyanine as molecular pedestals to immobilise the dyads onto the graphene thanks to a nanoporous network; and a perylenetetracarboxylic diimide, as the emissive component. This approach has been recently reported, however; we have found that the formation of these dyads is an intricate process, that requires an in-depth study of the solution phase before its study on a graphene surface. We demonstrate that two types of dyads can be formed in solution, depending on the supramolecular interactions that dominate the equilibrium, and the type of molecular pedesal used. A metal–ligand association was observed between the perylene and the porphyrin pedestal, whilst the phthalocyanine leads to a dyad formed via π–π interactions. We also conclude that scanning tunneling microscopy is not a reliable technique to characterise the on-surface assemblies, due to a strong probe–molecule interaction. Other spectroscopic techniques; such as epifluorescence micro-spectroscopy coupled with atomic force-microscopy, were investigated, however we found it is ambitious to rely solely on these techniques, to correlate observations from the nano to the micrometric scale.